The Shopping Behavior of Outsourced Employees at PT. Bukit Asam Tanjung Enim - Yuhendra, Yuhendra; Gunarto, Muji; helmi, Sulaiman (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the shopping behavior of outsourcing employees at PT. Bukit Asam Tanjung Enim, especially in terms of preferences, spending patterns, and the influence of the work environment on their shopping decisions. A qualitative approach is used to explore factors such as basic needs, lifestyle, and social pressures. The results of the study show that shopping behavior is influenced by fixed income, access to credit facilities, and promotions from digital platforms. This research provides important insights for local businesses to formulate relevant marketing strategies.